Mitologi Hijab: Meneropong Pergeseran Makna Hijab sebagai Simbol Keimanan dan Simbol Fashion Era Milenial di Indonesia - Muslih, Muslih (JOIES (Journal of Islamic Education Studies), 2017)
Multiinterpretations related to the definition and law of wearing hijab for Muslim women among interpreters, have a direct impact on society. Namely, some understand that wearing a hijab is an obligation for every Muslim woman. Some also understand that hijab is not an obligation but only a product of pre-Islamic Arab culture. this difference makes stretching hijab various kinds of motives, especially in the contemporary era like today. In the context of Indonesia's heterogeneous society, with various backgrounds of understanding Islamic teachings that vary in various levels also make the awareness to wear hijab also varied. There are those who are purely understanding the command to cover their genitals with hijab, some are due to follow a modern lifestyle that understands hijab as a fashion trend, and some understand hijab as a means of covering aurat and hijab as a fashion style in the present era. In this article, the author wants to explore how the hijab from the early historical aspects emerged, how from the Islamic Shari'a review, its development to the emergence of the hijab phenomenon in the contemporary era was only a style of dress without a spirituality like its wearer.